PUBLIC VALUES AND PUBLIC INTEREST - BARRY BOZEMAN (Georgetown University Press, 2007)
No deliberation of politics and political theory claims a more venerable heritage than the dialogues on the existence, nature, and requirements of the â€œpublic interestâ€ or the â€œcommon good.â€ In Aristotleâ€™s Politics, the â€œcommon interestâ€ (to koinei sympheron) is the rationale for proper constitutions; St. Thomas Aquinas in Summa Theologiae identifies the common good (bonum commune) as the worthy goal of government; Lockeâ€™s Second Treatise of Government declares that â€œthe peace, safety, and public good of the peopleâ€ are the transcendent political purposes. We need not go back hundreds of years to find interest in public interest theory. In the early years of the twentieth century, many prominent political scientists paid homage to the idea of the public interest. Pendleton Herringâ€™s (1936) reconciliation theory was premised on public managersâ€™ ability to divine the common good; Emmette Redford (1954) viewed the public interest as the key to effective regulatory administration; Phillip Monypenny (1953) anchored his public administration ethical code in a concept of the public interest. Even the foundation stone of American public administration, Woodrow Wilsonâ€™s (1955) Study of Administration, originally published in 1887, set its famous politics/administration dichotomy in a concept of the collective good (Rutgers 1997).